Marketing Research Efforts To Develop Products of Kerupuk Sanjai Bumbu Rendang - Bridha, Risya Ladiva; Ahman, Eeng; Priatini, Woro (Universitas Pendidikan Indonesia, 2019)
West Sumatra is a province that has a food characteristic of the region that is already known to the public, namely karupuak sanjai and rendang. Rendang with taste spicy and savory when paired with karupuak Sanjai the bargain, will surely give a new flavor to this historic food. Therefore, they invented a new product development of existing karupuak sanjai as souvenirs of West Sumatra is karupuak Sanjai bumbu rendang. Then karupuak Sanjai bumbu rendang will in consumer acceptance test, whether this new product can be accepted in the market or not. The method in this research using quantitative methods with experimental approaches and hedonic organoleptic test, test consumer acceptance, and his DKBM nutritional analysis. This study states that the product karupuak Sanjai rendang selected seasoning weighing 40 grams, the selected products compared with control products with significantly different results, karupuak Sanjai rendang seasoning has a higher nutritional value than at karupuak sanjai balado; karupuak sanjai bumbu rendang can be accepted by the community as the development of new products from previous karupuak sanjai.